Educational quality in Boyacá. Unfuturo under construction. 2024 -2034 - Soto Arango , Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2024)
Within the government policy of Governor Carlos Amaya 2024-2027, it is established that "The development of a society has knowledge and education as its fundamental axis; (basic, high school, technical and university)", and with the 2030 agenda of the UN, taking "territorial sustainable development" as its axis, it is proposed within these guidelines to guarantee, for the 15 provinces of Boyacá, quality education in different territorial contexts, promoting integration and communication between the different educational levels. In addition, it seeks to strengthen the structures of innovation and creativity, commenting on the relevance, inclusion and educational coverage. It also promotes community-bioethical educational entrepreneurship, which includes the integration of sports and productive practices in the field of STEAM.